A Novel Homozygous Splice Site Variant in AIMP1 Gene Causing Hypomyelinating Leukodystrophy: Case Report and Review of the Literature - Quental, Rita; Sampaio, Mafalda; Alonso, Isabel; Quental, Sofia; Leão, Miguel; Sousa, Raquel (Neuropediatrics, 2023)
Background Biallelic pathogenic variants in AIMP1 gene cause hypomyelinating leukodystrophy type 3, a severe neurodegenerative disorder with early onset characterized by microcephaly, axial hypotonia, epilepsy, spasticity, and developmental delay.Methods Clinical exome sequence was performed on patient's DNA and Sanger sequencing was used to confirm the candidate variant. To better characterize the effect of the genetic variant, functional analysis based on Sanger sequencing of the proband's complementary DNA (cDNA) was performed.Results We report a case of 2-year-old girl with microcephaly, significant global developmental delay, refractory epilepsy, flaccid paralysis, hypomyelination, leukodystrophy, and cerebral atrophy on brain magnetic resonance imaging (MRI). Clinical exome sequencing revealed a novel splice site variant c.603 + 1G > A in homozygosity in the AIMP1 gene. Studies on patient's cDNA showed that the variant disrupts the canonical donor splice site of intron 5, with the recognition of a cryptic splice site within exon 5, leading to the skipping of the last 24 nucleotides of this exon together with the flanking intron. This alteration is predicted to cause an in-frame deletion of eight amino acids (p.Val194_Gln201del) belonging to the tRNA-biding domain of the protein.Conclusion To the best of our knowledge, this is the first report of a splice site variant in the AIMP1 gene causing hypomyelinating leukodystrophy. The description of this patient not only expands the mutational spectrum of AIMP1 but also provides deeper insights on genotype–phenotype correlation by comparing the clinical features of our patient with previously reported affected individuals.
Keywords: AIMP1; hypomyelination; leukodystrophy; splicing; RNA; exome